The German "debt brake": Success factors and challenges - Lars P. Feld; Wolf Heinrich Reuter (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2021)
Germany introduced a new fiscal rule, the 'debt brake', after the Global Financial Crisis and since then experienced a strong decline in its public debt to GDP ratio until the coronavirus pandemic struck. The past ten years and the reaction to the current crisis in Germany illustrate the intended effects of fiscal rules very well. Debt ratios are reduced during normal economic times, such that fiscal policy can forcefully counteract a severe crisis. Escape clauses are therefore an essential part of the design of fiscal rules. Much of the success of fiscal rules depends on the public and political acceptance of the fiscal rules and thus high political costs of not complying with them. Furthermore, the design and framework of the rules among others by restricting cyclically adjusted figures and a strong legal anchoring are important. It will be important for Germany and other economies to repeat the reduction in the debt to GDP ratio in order to be prepared for the next unexpected crisis. This also means improving the design and framework of fiscal rules, e.g., by making the cyclical adjustment less uncertain and susceptible to revisions, improving the transparency of fiscal policy and rule compliance, as well as discussing as to how fiscal rules can contribute to improving the quality of public finances. However, an abolishment of fiscal rules would hamper the ability of fiscal policy to cope with the long-term challenges and to prepare for unexpected short-term challenges.
Keywords: H62; H63; D78; 330; Public Debt; Fiscal Policy; Fiscal Rules